Effects of whole-body electromyostimulation exercise and caloric restriction on cardiometabolic risk profile and muscle strength in obese women with the metabolic syndrome: a pilot study - Reljic, Dejan; Konturek, Peter; Herrmann, H. J.; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2020)
Obesity, particularly in conjunction with further cardiometabolic risk factors, is associated with an increased risk of cardiovascular disease and mortality. Increased physical activity and dietary modifications are cornerstones of therapeutic interventions to treat obesity and related risk factors. Whole-body electromyostimulation (WB-EMS) has emerged as an innovative, time-efficient type of exercise that can provide positive effects on body composition and muscle strength. However, the impact of WB-EMS on cardiometabolic health in obese individuals with metabolic syndrome (MetS) has yet to be determined. The aim of this pilot study was, therefore, to investigate the feasibility and effects of WB-EMS on cardiometabolic risk markers and muscle strength in obese women diagnosed with MetS. Twenty-nine obese women (56.0 ± 10.9 years, BMI: 36.7 ± 4.6 kg/m2) with the clinical diagnosis of MetS were randomized to either 12 weeks of WB-EMS (n = 15) or an inactive control group (CON, n = 14). Both groups received nutritional counseling (aim: -500 kcal energy deficit/day). WB-EMS was performed 2x/week (20 min/session). Body composition, maximum strength (Fmax) of major muscle groups, selected cardiometabolic risk indices and the metabolic syndrome Z-score (MetS-Z) were determined baseline and after the intervention. WB-EMS was well tolerated and no adverse events occurred. Body weight was significantly reduced in both groups by an average of 3 kg (P < 0.01). The body fat percentage was only decreased in the WB-EMS group (P = 0.018). Total cholesterol concentrations decreased in the WB-EMS group (P = 0.018) and in CON (P = 0.027). Only the WB-EMS group increased Fmax significantly in all major muscle groups (P < 0.05) and improved the overall cardiometabolic risk score (MetS-Z, P = 0.029). This pilot study indicates that WB-EMS can be considered as a feasible and time-efficient exercise option for improving body composition, muscle strength and cardiometabolic health in obese women with MetS. Moreover, these findings underpin the crucial role of exercise during weight loss interventions in improving health outcomes.
CRIS-Team Scopus Importer:2020-06-30